HUBUNGAN KUALITAS SISTEM, KUALITAS INFORMASI, DAN KUALITAS LAYANAN DENGAN KEPUASAN PENGGUNA SISTEM INFORMASI PADA APLIKASI DEPOK SINGLE WINDOW (DSW) DI KOTA DEPOK - Rasya Fauzia, Alya; Hayu Dwimawanti, Ida; Puspo Priyadi, Budi (Journal of Public Policy and Management Review, 2024)
The rapid development of the digital era demands that governments adapt in delivering public services through the implementation of electronic government (e-Government). Depok, as the city with the third-highest number of internet users in Indonesia, strives to leverage information and communication technology to facilitate interaction between the government and the public. This effort is supported by the creation of the Depok Single Window (DSW) application, a mobile app that serves as a single portal for public services in Depok. However, several issues indicate that the system, information, and services provided by the Depok Single Window application do not fully meet user satisfaction, as evidenced by user reviews on the Play Store, App Store, Instagram, and Twitter. This study aims to analyze the relationship between system quality, information quality, and service quality and user satisfaction with the Depok Single Window information system, using the information system user satisfaction theory by DeLone and McLean (2003). This research employs a quantitative approach with an explanatory method. The sampling technique used in this study is Non-Probability Sampling with a Purposive Sampling method, while data collection was conducted through a questionnaire distributed via Google Forms. The results of the study indicate that system quality has a partially positive and significant relationship with user satisfaction, with a t-value of 6.331. Information quality has a partially positive and significant relationship with user satisfaction, with a t-value of 4.536. Service quality has a partially positive and significant relationship with user satisfaction, with a t-value of 2.490. System quality, information quality, and service quality simultaneously have a positive and significant relationship with user satisfaction, with an F-value of 248.704.